A Note on the Yamabe Problem (Journal of Partial Differential Equations, 2020)
In this note we verify the key inequality Y_1(M) < Y_1(S^n) for the Yamabe constant Y_1(M) for manifolds M not conformal to the unit sphere, by using a solution to an associated equation as a test function.